"The race was on trial": Migrant adjustment in Philadelphia and Pittsburgh during the great migration - Nina Banks (Essays in Economic & Business History (EEBH), 2023)
This essay provides the first comparison of the political economic thought of Sadie T.M. Alexander and Abram Harris Jr., the first Black American economists, through an analysis of Alexander's dissertation and Harris' master's thesis. Alexander and Harris studied the Great Migration of Black Americans from the South to northward destinations while the early migration was unfolding. Reflecting the anxieties of northern Black residents, Alexander and Harris' research explored the racial implications of migration on Black communities in Philadelphia and Pittsburgh Pennsylvania, respectively, through an analysis of migrants' ability to adjust to their new urban environments. I examine Alexander and Harris' understanding of migrant adjustment, their methods for analyzing adjustment, and their recommendations for facilitating migrants' adjustment to northern industrial economies. Alexander and Harris' analyses of the Great Migration differed from later generations of mostly White economists in ways that can inform directions for future research on the migration.
Keywords: B15; B31; N92; 330; Great Migration; Sadie Alexander; Abram Harris Jr; Migrant Adjustment